Proteome changes and physiological adaptations of the phytopathogen Xanthomonas citri subsp. citri under salt stress and their implications for virulence. Issue 6 (31st May 2019) - Barcarolo, María Victoria; Garavaglia, Betiana S; Thomas, Ludivine; Marondedze, Claudius; Gehring, Chris; Gottig, Natalia; Ottado, Jorgelina
ABSTRACT: The bacterium Xanthomonas citri subsp . citri (Xcc) is responsible for the widely distributed disease citrus canker. In the last years, Xcc has become a model for the study of plant pathogens, and here we used this bacterium to examine stress on the pathogen during adaptions required for leaf colonization. In the first stages of citrus canker cycle, bacteria encounter low water availability and osmotic stress that can affect their maintenance on plant surfaces. To examine such conditions, we conducted a proteome analysis of Xcc grown in culture medium supplemented with 0.25 M sodium chloride and compared it to control conditions. We found that salt stress induced changes in known stress-induced proteins and also revealed novel stress response proteins. Moreover, some of the bacterial processes associated with bacterial fitness and virulence were modified under salt stress conditions. In particular, swimming, twitching and surface motilities were decreased, while biofilm formation was increased under salt stress. Other adaptations to high salt included reduced bacterial size and increased survival of bacteria exposed to oxidative stress. Furthermore, expression of type III protein secretion system related genes were augmented under salt stress condition. Our results offer new insight into molecular mechanisms that govern phytopathogen adaptation to harsh environments. These adaptations affect life cycle progression which in turn influences virulence. Abstract : Responses of the pathogen responsible for citrus canker to salt stress.